Frontal and lateral characteristics of the osseous configuration in chronic ankle instability. Issue 8 (4th July 2008) - Magerkurth, O; Frigg, A; Hintermann, B; Dick, W; Valderrabano, V
Abstract : Objective: The osseous ankle configuration (tibiotalar sector, talar radius and height) has been discovered as intrinsic risk factor for chronic ankle instability (CAI). These measurements were done on lateral radiographs only. In this study, the osseous characteristics in the frontal plane and further lateral values were measured. Design: Level III case-control study. Setting: Radiological measurement of frontal and lateral radiographs by one independent, blinded radiologist using a digital DICOM/PACS system. Patients: A group of 52 patients with CAI was compared with an age- and sex-matched control group of 52 healthy subjects. Main outcome measurements: In the frontal plane, the depth of the talar curvature (frontal curvature (froCu)) and the lateral and medial malleolar lengths were measured. In the lateral plane, the position of the centre of rotation to the tibial axis (talar centre of rotation to the anatomical axis of the tibia (TibCOR)) and the tibial lateral surface angle (TLS) were also measured. Results: The froCu was deeper in patients with CAI (1.8 (0.5) mm) than in healthy subjects (1.0 (0.5) mm, p<0.05). The TibCOR was more anterior in patients with CAI (2.5 (1.9) mm) than in healthy subjects (1.6 (2.2) mm, p<0.05). The distance from the fibular tip to the centre of rotation was smaller in patients with CAI (3.5 (3.4) mm) than in healthy subjects (6.5 (3.3) mm, p<0.05). The TLS and the length of the lateral and medial ankle were not significantly different. Conclusions: This study supports that the osseous joint configuration is an intrinsic risk factor for CAI. It could be shown that CAI is characterised by a deeper frontal curvature of the talus and a more anterior position of the talus to the tibia.